Analisis Peran Digitalisasi Marketing Sertifikasi Halal Dan Product Knowledge Bagi Kemajuan Ekonomi Kreatif - Rohama Ubainahum; Anzu Elvia Zahara; G.W.I Awal Habibah (Universitas Sains dan Teknologi Komputer, 2024)
The purpose of this research is to find out the role of marketing digitalization, halal certification and product knowledge. The results of this study show that, first, the role of marketing digitalization facilitates the business of the creative culinary industry in the city of Jambi, including (1) finding consumers, (2) flexible media in promotion, (3) the choice of digital marketing platforms as needed so that they can divert the budget to programs more effectively and, (4) To increase the sales volume, it can carry out management periodically. Second, the role of halal certification is; (1) ensuring that the products that have been produced are avoided from harmful substances and, (2) a form of increasing halal awareness. The third role of product knowledge for creative culinary industry businesses in Jambi City as an understanding of needs is; (1) maintaining human welfare protecting the wealth spent towards the path of goodness, (2) The role of product knowledge as an understanding of the existence of a reciprocal relationship between entrepreneurs and consumers towards products.